Tales of Horror - Nikesh Murali; MURALI (Nikesh) (New Delhi Prakash books India Pvt.Ltd, 2023)
Prepare to immerse yourself into the heart of darkness as Nikesh Murali, Commonwealth Short Story Prize-winning author and creator of India's most critically acclaimed horror podcast Indian Noir weaves an unforgettable tapestry of bone-chilling scares and unrelenting terror. Whether you're a seasoned horror enthusiast or a newcomer to the genre, this anthology is sure to satisfy your cravings for all things terrifying.By the host of the no. 1 podcast 'Indian Noir'A collection of unique and original horror storiesFeatures immersive world-building, creating a sense of place and atmosphere that can transport readers to a different time, place, or even dimensionExplores deeper themes, such as trauma, fear, and mortalityGenerates a powerful emotional response in readers
Keywords: English Fiction